2018
DOI: 10.1590/1983-1447.2017.03.2016-0060
|View full text |Cite
|
Sign up to set email alerts
|

A utilização de instrumentos para avaliação da liderança nos serviços de saúde e enfermagem

Abstract: RESUMO Objetivo Identificar as evidências científicas disponíveis acerca da utilização de instrumentos para a avaliação da liderança nos serviços de saúde e enfermagem, bem como verificar a utilização de estilos/modelos/teorias de lideranças na construção dos mesmos. Método Revisão integrativa da literatura de estudos indexados nas bases de dados LILACS, PUBMED, CINAHL e EMBASE, no período de 2006 a 2016. Resultados 38 artigos foram analisados, exibindo 19 instrumentos de avaliação da liderança, sendo os ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 54 publications
(136 reference statements)
1
6
0
12
Order By: Relevance
“…An integrative literature review study on leadership assessment tools found that "the transformational leadership model contributed to increased motivation and job satisfaction by providing collective discussion, broadening dialogical communication and active listening to workers, leading to greater commitment" (12) corroborating the findings in this research.…”
Section: Discussionsupporting
confidence: 78%
“…An integrative literature review study on leadership assessment tools found that "the transformational leadership model contributed to increased motivation and job satisfaction by providing collective discussion, broadening dialogical communication and active listening to workers, leading to greater commitment" (12) corroborating the findings in this research.…”
Section: Discussionsupporting
confidence: 78%
“…An integrative review has shown that situational leadership has been one of the leadership models most used by nurses (Carrara et al, ). The situational leadership approach of Hersey and Blanchard () is one of the contingency approaches.…”
Section: Introductionmentioning
confidence: 99%
“…(26) Leading in times of COVID-19 implies transformational leadership, which contributes to increasing motivation and job satisfaction for professionals, promoting communication and active listening, leading to organizational commitment. (27) This approach guarantees quality care, namely nursing care, in the field of management, education, as well as assistance (28) , so this leadership style should be privileged by all managers in the health area, namely nurse managers.…”
Section: The Covid-19 Pandemic: Repercussions On the Organizational Culture And Professional Practice Of Specialist Nurses And Nurse Manamentioning
confidence: 99%